The Effect of Human Resources Management Practice on School Productivity in Private School - Ndoa, Paulinus Kanisius; Satori, Djam’an; Herawan, Endang; Nurdin, Diding; Sumiati, Sumiati (JETL (Journal of Education, Teaching and Learning), 2025)
This paper examines the factors that contribute towards enhancing Labor productivity. The research method employed was quantitative, with it employing a survey-based methodology. The study’s population comprised 78 participants including principal, teachers, and staffs in Catholic private schools under Sibolga diocese. Proportional random sampling was used to select a sample of people. A questionnaire was designed in order to collect data, with this passing the validity and reliability tests and meeting the necessary characteristics for a good instrument. Smart PLS 3.0 was employed to evaluate the gathered data. Four components to consider to be human resources management practices including human resources planning, job analysis, recruitment, and selection.  The study found a positive relationship between human resources management and school productivity.